Manual Dexterity Is a Strong Predictor of Visuo-Motor Temporal Integration in Children - Nobusako, Satoshi; Sakai, Ayami; Tsujimoto, Taeko; Shuto, Takashi; Nishi, Yuki; Asano, Daiki; Furukawa, Emi; Zama, Takuro; Osumi, Michihiro; Shimada, Sotaro; Morioka, Shu; Nakai, Akio (Frontiers in Psychology, 2018)
Although visuo-motor temporal integration in children is suggested to be related to motor control and motor learning, its relevance is still unclear. On the other hand, visuo-motor temporal integration ability undergoes developmental changes with age. In the current correlational study, we measured manual dexterity and visuo-motor temporal integration ability in 132 children with typical development (age, 4–15 years) and investigated the relationship between the two functions. The Movement Assessment Battery for Children-2nd edition was used as an indicator of manual dexterity. The delay detection threshold (DDT) and steepness of the probability curve for delay detection, which was measured by the delayed visual feedback detection task for self-generated movement, were used as indices of the visuo-motor temporal integration ability. The results indicated significant correlations between manual dexterity/age and DDT/steepness of the probability curve for delay detection. In addition, hierarchical multiple regression analysis showed that both manual dexterity and age significantly contributed to visuo-motor temporal integration, indicating a better fit than when only age was employed as an independent variable. Importantly, there was no interaction effect between age and manual dexterity. These findings were the first to suggest that manual dexterity is a significant predictor of visuo-motor temporal integration ability in children, regardless of age. The present study validated the important relationship between visuo-motor temporal integration and manual dexterity in children. Considering the limitations of the current study, including the non-homogeneous sample, further studies are still warranted to validate the results.